Reduction of cardiovascular disease inequalities in the USA through dietary policy. (November 2016) - Pearson-Stuttard, Jonathan; Bandosz, Piotr; Rehm, Colin; Penalvo, Jose; Whitsel, Laurie; Gaziano, Tom; Conrad, Zach; Wilde, Parke; Micha, Renata; Lloyd-Williams, Ffion; Capewell, Simon; Mozaffarian, Dariush; et al.
Abstract: Background: The burden of cardiovascular disease mortality remains large and unequal in the USA, and is mostly attributable to poor diet. Few data exist about the potential population level impact on inequalities of policies to improve diet such as the Supplemental Nutrition Assistance Program (SNAP). We aimed to estimate reductions in cardiovascular disease mortality and inequalities achievable in the US population up to 2030 through dietary policies. Methods: We developed a US IMPACT (International Model for Policy Analysis of Agricultural Commodities and Trade) food policy model to estimate the number of deaths prevented or postponed (DPPs) achievable with four feasible scenarios that have been successfully implemented across the world: a national fruit and vegetables and sugar-sweetened beverage mass media campaign, fruit and vegetable price reductions of 10% universally and 30% to SNAP participants, and universal sugar-sweetened beverage price increase of 10%. We further modelled a combination of these policies. We stratified the US population by SNAP eligibility and participation. We estimated number of deaths using the incremental effect of each policy upon the target food groups. Then we estimated the effect upon cardiovascular disease mortality compared with existing baseline of continued trends. Probabilistic sensitivityanalyses were conducted. Findings: A universal 10% price reduction of fruit and vegetables could prevent the most deaths—about 150 500 DPPs by 2030 (95% CI 137 800–160 500). This compares with approximately 23 000 DPPs (21 500–24 600) generated through a 1 year mass media campaign, or 21 400 DPPs (18 200–24 500) by a 10% price increase in sugar-sweetened beverages. A 30% price reduction in fruit and vegetables for SNAP participants could result in roughly 35 100 DPPs (31 800–37 700) and also achieve the biggest reduction in inequalities between SNAP participants and the ineligible population. The combined policy approach would save most lives (about 204 800 DPPs) while also reducing inequalities. Interpretation: Fiscal strategies targeting diet could contribute to reduce the unequal cardiovascular mortality burden in the USA. All four dietary policies would be effective, but a combination of the universal and targeted aspects of policies would be the most effective. Individually, a universal 10% reduction in the price of fruit and vegetables might save most lives, whereas a targeted, 30% price reduction for SNAP participants could reduce inequalities the most. Funding: National Institutes of Health (grant number R01HL115189 ). The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the abstract.